VALIDITAS MEDIA DIGITAL BERBASIS KEARIFAN LOKAL BATIK JAMBI UNTUK PEMBELAJARAN IPAS PERUBAHAN WUJUD ZAT KELAS IV - Rut Putri Rajagukguk; Destrinelli Destrinelli; Desy Rosmalinda (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research focuses on the development of a digital learning media that highlights the local wisdom of Jambi Batik as a learning context for the material of changes in the state of matter for fourth grade elementary school students. The use of local cultural elements is expected to make the concept of science and natural sciences feel more concrete, meaningful, and close to the daily experiences of students, thereby helping them understand the material more easily. The method used is research and development (R&D) with the DDD-E model which includes the stages of Decide (determining needs and objectives), Design (media design), Develop (product creation and refinement), and Evaluate (assessment and improvement). Data were obtained through interviews, observations, and questionnaires. After the media was developed, a validation test was conducted to assess its feasibility and quality, involving three validators, namely media experts, material experts, and language experts. The validation results showed an average score of 95% from media experts with a feasible category, 97.5% from material experts with a very feasible category, and 98% from language experts with a feasible category. Based on these findings, the digital learning media based on the local wisdom of Jambi Batik on the material of changes in the state of matter for fourth grade elementary school students is declared to meet the eligibility criteria and can be used as an alternative media in classroom learning activities. ABSTRAKPenelitian ini difokuskan pada pengembangan sebuah media pembelajaran digital yang mengangkat kearifan lokal Batik Jambi sebagai konteks pembelajaran materi perubahan wujud zat untuk siswa kelas IV Sekolah Dasar. Pemanfaatan unsur budaya lokal tersebut diharapkan dapat membuat konsep IPAS terasa lebih konkret, bermakna, dan dekat dengan pengalaman sehari-hari peserta didik, sehingga membantu mereka memahami materi dengan lebih mudah. Metode yang digunakan adalah penelitian pengembangan (Research and Development/R&D) dengan model DDD-E yang meliputi tahapan Decide (penentuan kebutuhan dan tujuan), Design (perancangan media), Develop (pembuatan dan penyempurnaan produk), serta Evaluate (penilaian dan perbaikan). Data diperoleh melalui wawancara, observasi, dan penyebaran angket. Setelah media selesai dikembangkan, dilakukan uji validasi untuk menilai kelayakan dan kualitasnya, melibatkan tiga validator, yaitu ahli media, ahli materi, dan ahli bahasa. Hasil validasi menunjukkan skor rata-rata persentase 95% dari ahli media dengan kategori layak, 97,5% dari ahli materi dengan kategori sangat layak, serta 98% dari ahli bahasa dengan kategori layak. Berdasarkan temuan tersebut, media pembelajaran digital berbasis kearifan lokal Batik Jambi pada materi perubahan wujud zat untuk siswa kelas IV SD dinyatakan memenuhi kriteria kelayakan dan dapat digunakan sebagai salah satu alternatif media dalam kegiatan pembelajaran di kelas.